2003
DOI: 10.1210/jc.2002-020788
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Two Ovarian Stimulation Protocols with Gonadotropin-Releasing Hormone (GnRH) Antagonist Cotreatment forin VitroFertilization Commencing Recombinant Follicle-Stimulating Hormone on Cycle Day 2 or 5 with the Standard Long GnRH Agonist Protocol

Abstract: Extending the FSH window for multifollicular development by administering FSH from the midfollicular phase onward constitutes a novel mild protocol for ovarian stimulation for in vitro fertilization (IVF) based on the physiology of single dominant follicle selection in normo-ovulatory women. We compared outcomes from this protocol with two other stimulation protocols. One hundred and forty-two normo-ovulatory patients with an indication for IVF (or IVF/ICSI) were randomized to a GnRH agonist long protocol (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
98
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(115 citation statements)
references
References 44 publications
11
98
0
5
Order By: Relevance
“…In our study, the FSH dose and the number of retrieved oocytes had a negative impact on the TE quality. Our results are in agreement with recent studies that have shown that milder ovarian stimulation reduces the likelihood of segregation errors during early embryo cleavages [16,22] and results in high-quality embryos for transfer, as indicated by good embryo morphology [17]. The observation that higher FSH doses and oocyte yields are associated with impaired blastocyst development may be due to an supraphysiologic ovarian stimulation that interferes with the cell machinery during oocyte formation.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the FSH dose and the number of retrieved oocytes had a negative impact on the TE quality. Our results are in agreement with recent studies that have shown that milder ovarian stimulation reduces the likelihood of segregation errors during early embryo cleavages [16,22] and results in high-quality embryos for transfer, as indicated by good embryo morphology [17]. The observation that higher FSH doses and oocyte yields are associated with impaired blastocyst development may be due to an supraphysiologic ovarian stimulation that interferes with the cell machinery during oocyte formation.…”
Section: Discussionsupporting
confidence: 92%
“…Five retrieved oocytes were associated with an ideal ongoing pregnancy rate (67 %) per embryo transfer in patients undergoing a mild stimulation protocol using GnRH-antagonist [49,50]. On the other hand, a development of less than five follicles in a standard stimulation protocol is usually associated with poor outcome related to the low number transferred embryos and high cancellation rate due to the fertilization failure [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that mild ovarian stimulation, leading to a lower oocyte yield, is associated with a decrease in the proportion of aneuploid embryos [37]. A previous study also showed that mild stimulation resulted in high-quality embryos for transfer, as indicated by good embryo morphology [38].…”
Section: Discussionmentioning
confidence: 98%